(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he main goal of the present paper is to demonstrate that the study of church subsidies constitute a viable investigation line and path in order to ind out more about church policies and the New Hispanic Church in Philip v’s era, a period that has been little studied. In that regard, it needs to be pointed out that in the historiography of the modern era of Spain, Philip v’s reign is generally labelled as a “projectist” period, meaning that it welcomed the irst attempts to carry out reforms. hese reformist tendencies need to be linked with the events of the so-called Western Indies in the same period, as serious attempts to change church policies can be observed here. In this sense, the study of the introduction of church subsidies, as well as its consequences in the New Hispanic church and clergy, can be a feasible path as it closely shows the formulation of the irst reform plans of the Bourbons towards the Indian Church in the irst decades of the 18th century.